Estudo da correlaÃÃo dos nÃveis sÃricos de citocinas (IL-1β, IL-6, IL-18BP, IL-33 E TNF-α) e da atividade da mieloperoxidase com o grau de obstruÃÃo coronariana em pacientes com hipÃtese diagnÃstica de doenÃa isquÃmica do miocÃrdio - AntÃnio Augusto GuimarÃes Lima (2012)
Atherosclerosis is a complex multifactorial disease characterized by accumulation of inflammatory cells, lipoproteins, and fibrous tissue in the walls of large and medium arteries. The innate and adaptive immunity, with the presence of leukocytes, mainly monocytes and lymphocytes, have an important role in this process. This participation can take place by signaling with cytokines and the release of the enzyme myeloperoxidase (MPO) by the cytoplasmic granules. Cardiovascular risk factors classically play an important role in prevention, however, the majority of patients with CV events have one or no risk factor. Therefore new biomarkers are needed to define diagnosis and prognosis. This study selected patients with a diagnosis of stable angina (SA) or acute coronary syndrome (ACS) undergoing coronary angiography and evaluated by the Gensini score (GS). Performed serum activity MPO, serum tumor necrosis factor alpha (TNF-α), interleukins (1β, 6, 18bp and 33) (IL-1β, IL-6, IL-18bp, and IL-33, respectively). In two years carried out a review of medical records or telephone interviews in 93 patients in this sample. Used to analyze the variables: atherosclerotic burden (carotid, coronary or lower limb atherosclerosis); the clinical picture in two years (asymptomatic or chest pain or death); clinical presentation (SA or ACS); cardiovascular events (stent, CABG, chest pain or death). The results combinations of cytokines and myeloperoxidase, with the variables presented demonstrate that IL-6 related in univariate analysis with the presence of atherosclerotic load (p <0.014), elevated serum levels of IL-18bp in patients with ACS both in univariate and multivariate analysis (p <0.001 and p <0.045 respectively), IL-1β was negatively correlated with the degree of GS in univariate and multivariate analysis (p <0.042 and <0.002 respectively); in a univariate analysis associated with the GS on patients who had chest pain or death, undergoing CABG, with CV events and ACS (p <0.001 for all). In multivariate analysis, patients with higher GS underwent CABG more often and had more chest pain or death (p <0.001 for all). The MPO activity showed no correlation or association with different variables. Patients with diabetes mellitus and in use of statin had higher GS (p <0.001 for both). In conclusion, patients with coronary stenosis were important predictors of cardiovascular events and more often underwent CABG. The IL-1β correlated negatively with GS and patients with at least one of the sites previously mentioned atheroclerosis had IL-6 levels elevated. IL-18bp correlated with elevated serum levels in patients with ACS.